Aligning supply chain complexity with product demand and design characteristics. Issue 8 (3rd August 2022) - Chhetri, Prem; Hashemi, Amirreza; Lau, Kwok Hung; Lim, Ming K.
ABSTRACT: This study models the alignment of supply chain complexity with product demand and design characteristics and formulates appropriate strategies to enhance supply chain alignment. An integrated theoretical framework linking all the three main constructs of supply chain complexity, namely, coordination, collaboration, and configuration, with product demand and design complexities is developed and empirically tested. Data were collected from a cross-industry sample of 273 Australian manufacturing firms and analysed using structural equation modelling. The results show that volatility of demand, product life cycle, and innovativeness directly impact on the complexity of supply chain collaboration. Product modularity, on the other hand, is more likely to indirectly influence supply chain collaboration through the mediating role of coordination. Higher complexity in product demand and design characteristics increases complexity in supply chain coordination and configuration while reducing complexity in supply chain collaboration. Based on the findings, a taxonomy is proposed to provide a reference frame for practitioners to formulate appropriate alignment strategies to manage or mitigate risk associated with growing supply chain complexity.